Optimisation of Ammonium Tartrate and Glucose Concentration for Gamma Linolenic Acid Production by Cunninghamella sp 2A1 - Muhid, F; Kader, AJA; Yusoff, WMW; Omar, O; Hamid, AA (Univ Kebangsaan Malaysia, 2024)
Indexed by Scopus